Heterangaeus Alexander, 1925 crane flies (Diptera: Pediciidae) of Korea - Podenas, Sigitas; Podeniene, Virginija; Byun, Hye-Woo (Zootaxa, 2015)
The Korean crane fly species of the genus Heterangaeus Alexander, 1925 (Diptera: Pediciidae) is taxonomically revised. H. gloriosus gloriosus (Alexander, 1924) is redescribed. A new species Heterangaeus koreanus n. sp., which is the first species of Pediciidae from South Korea, is described and illustrated.